STRATEGI KEWIRAUSAHAAN TERHADAP BUSINESS PERFORMANCE DIMEDIASI KEMAMPUAN KREATIVITAS DAN INOVASI PADA USAHA GARMEN DI PASAR TRADISIONAL BANDUNG - Rizki Zulfickar; Amir Machmud; A. Sobandi (Edunomic : Jurnal Ilmiah Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan, 2020)
ABSTRACTThe purpose of this research is to find out the effect of Entrepreneurship Strategy on Business Performance mediated by the ability of Creativity and Innovation in Garment Business in Bandung Traditional Market. Study population, 280 Bandung garment businesses. Determination of sample size uses the Slovin formula with a sample size of 165 Bandung garment businesses.. Data collection techniques using a questionnaire. Data analysis uses descriptive statistical analysis and Multiple Mediation Regression analysis. Descriptive analysis of results obtained that the Business Performance in the good category, Entrepreneurship Strategy in the good enough category, Creativity in the good enough category, and Innovation in the good enough category. The results showed that the Entrepreneurship Strategy directly involved Business Performance with a coefficient of determination of (57.7%). Mediation effect through creativity with a coefficient of determination of (19.1%), mediation effect through innovation with a coefficient of determination of (16.7%), total mediation effect of Creativity and innovation with a coefficient of determination of (81.5%). The conclusions of the research related to the Entrepreneurship Strategy simultaneously on Business Performance are mediated by Creativity and Innovation in the Garment Business in Bandung Traditional Market.Keywords: Entrepreneurship Strategy, Creativity Ability, and Innovation, Business Performance